The impact of mental health stigma in a young Malaysian lady with recurrent suicidal ideations and moribund presentations to the Emergency Department: a case report - Petrus, Chiara Francine; Mohd Salleh Sahimi, Hajar; Midin, Marhani; Lim, Jane Tze Yn (Frontiers in Psychiatry, 2023)
Mental health stigma (MHS) has been a pervasive social issue and a significant barrier to treatment seeking behavior. The treatment pathways and outcomes for people with mental illness, specifically those with recurrent suicidal ideations and attempts have been influenced by how MHS was experienced in clinical practice.We reported a case of a young lady diagnosed with bipolar II disorder, obsessive-compulsive disorder and borderline personality disorder who had recurrent visits to various emergency departments (ED) of tertiary hospitals in Malaysia for suicidality; each time presenting with increased mortality risk and escalating near-lethal outcomes. Amongst the multiple ED visits after her alleged overdoses of psychotropic medications, thrice she was near-unconscious and had to be intubated for airway protection, subsequently requiring ventilatory support and ICU care. These nearlethal presentations in ED were due to her delays in seeking treatment for fear of re-experiencing the stigmatizing environment among healthcare staff and professionals in the ED.The impact of MHS is detrimental. Effective interventions at various levels in the clinical setting is of utmost importance to prevent the negative consequences of suicidality against MHS.